Determination of heavy metals, nitrate and nitrite in mineral and drinking bottled water in Tehran, Iran: A health risk assessment by Monte-Carlo simulation method - Ramin Aslani; Saeideh Esmaeili; Mohamad Esmaeil Akbari; Ebrahim Molaee-Aghaee; Parisa Sadighara; Shahrokh Nazmara; Babak Mahmoudi (Heliyon)
Heavy metals, nitrate, and nitrite pose significant risks to public health and have raised substantial concern worldwide. This study aimed to investigate the content of nitrate, nitrite, and heavy metals, including Ba, Be, Ca, Fe, K, Li, Mg, Mn, Mo, and Na, in 30 bottled water brands in winter and summer in Tehran, Iran. Heavy metal contents in the samples were analyzed using Inductively Coupled Plasma Optical Emission Spectroscopy (ICP-OES), and nitrate and nitrite contents were analyzed using Ion Chromatography (IC). Nitrate concentrations ranged from 0.28 to 38.87 mg/L, and nitrite contents ranged from 0.001 to 0.13 mg/L. The mean concentration of Ba, Ca, K, Li, Mg, Mn, and Na in the bottled drinking water brands were 11.30, 7874.40, 121.27, 2.52, 4960.49, 0.22, and 12321.70 μg/L; and in the bottled mineral water brands were 15.71, 12262.05, 166.38, 4.13, 3747.07, <LOD, and 3156.81 μg/L. The contents of Be and Mo in all brands were below the limit of detection. Nitrate and nitrite concentrations exceeded those specified on their labels in 50 % of samples. Mg content in 4 brands and Na content in 10 brands were higher than the values listed on the labels. Furthermore, non-carcinogenic health risk assessment through bottled water consumption was estimated for Iranian children and adults. HQ values of nitrate, nitrite, Ba, Fe, Li, and Mn were less than one and acceptable. The results indicated that bottled water consumption cannot pose a significant health risk for Iranian adults and children.